2011
DOI: 10.1136/annrheumdis-2011-200085
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and physical interaction of the B-cell systemic lupus erythematosus-associated genes BANK1 and BLK

Abstract: Objectives Altered signaling in B-cells is a predominant feature of systemic lupus erythematosus (SLE). The genes BANK1 and BLK were recently described as associated with SLE. BANK1 codes for a B-cell-specific cytoplasmic protein involved in B-cell receptor signaling and BLK codes for an Src tyrosine kinase with important roles in B-cell development. To characterize the role of BANK1 and BLK in SLE, we performed a genetic interaction analysis hypothesizing that genetic interactions could reveal functional path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 28 publications
2
68
0
Order By: Relevance
“…Lyn-knockout mice develop severe lupus-like disease consistent with lack of regulatory signaling. On the other hand, Blk-and Fyn-knockout mice do not develop autoimmunity (18,19). However, BLK is implicated in negative regulation of BCR signaling (18,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lyn-knockout mice develop severe lupus-like disease consistent with lack of regulatory signaling. On the other hand, Blk-and Fyn-knockout mice do not develop autoimmunity (18,19). However, BLK is implicated in negative regulation of BCR signaling (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Blk-and Fyn-knockout mice do not develop autoimmunity (18,19). However, BLK is implicated in negative regulation of BCR signaling (18,19). Lyn mediates its inhibitory effects by phosphorylation of plasma membrane receptors such as CD22, CD72, and FcγRIIB, which act in turn by recruiting protein and inositol phosphatases (SHP-1 and SHIP-1, respectively) (20).…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported potential epistasis between BLK and TNFSF4 in both Chinese and white populations, suggesting that unbalanced functions of B cell and T cell signaling may be involved synergistically in the pathogenesis of SLE 2 . Another large-scale association study confirmed the genetic interactions between BANK1 and BLK in Europeans, indicating B cell activity and a B cell-specific pathway were crucial in lupus pathogenesis 3 . No further replications were conducted in Chinese subjects or other populations with independent sets of cases and controls.…”
Section: To the Editormentioning
confidence: 80%
“…The study was approved by the medical ethics committee of Peking University; all patients gave informed consent. The reported single-nucleotide polymorphisms (SNP) with top association signals of interactions were selected without optional discrimination 3 . Genotyping was undertaken as reported 2 .…”
Section: To the Editormentioning
confidence: 99%
“…Among these signaling molecules, BANK1, a positive regulator of the BCR signaling pathway, has been identified by GWAS to be a susceptibility gene for SLE. The diseaseassociated variants of BANK1 are found to induce sustained BCR signaling and B cell hyperactivity, leading to the proliferation and expansion of autoreactive B cells [129,130]. Several negative regulators of BCR signaling have also been associated with autoimmunity, including PTPN22, Csk, Lyn, CD22, and FcγRIIB.…”
Section: Genes That Affect B Cell Activationmentioning
confidence: 98%